Pathology of childhood rhabdomyosarcoma: A consensus opinion document from the Children's Oncology Group, European Paediatric Soft Tissue Sarcoma Study Group, and the Cooperative Weichteilsarkom Studiengruppe. Issue 3 (11th December 2020) - Rudzinski, Erin R.; Kelsey, Anna; Vokuhl, Christian; Linardic, Corinne M.; Shipley, Janet; Hettmer, Simone; Koscielniak, Ewa; Hawkins, Douglas S.; Bisogno, Gianni
Abstract: The diagnosis and classification of rhabdomyosarcoma (RMS) has undergone several shifts over the last 30 years. While the main diagnostic categories remained the same, changes in the histologic criteria necessary for diagnosis, as well as varied reliance on immunohistochemical and molecular data over time, have created confusion, particularly regarding how these shifts impacted risk stratification and enrollment onto clinical trials. The goal of this report is to review the evolution and current status of RMS diagnosis, focusing on diagnostic criteria in the Children's Oncology Group (COG), the European Paediatric Soft Tissue Sarcoma Group (EpSSG), and the Cooperative Weichteilsarkom Studiengruppe (CWS). In addition, we emphasize research tools used to classify RMS and address biological questions within current clinical trials run by each group. The INternational Soft Tissue SaRcoma ConsorTium (INSTRuCT) initiative will maximize potential to optimize risk stratification by recognizing and accounting for differences in historical data and current practices.